1990
DOI: 10.1111/j.1365-2125.1990.tb03701.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of the specific cholecystokinin receptor antagonist loxiglumide on cholecystokinin clearance from plasma in man.

Abstract: Saline or loxiglumide (2.5 mg kg-' in 10 min, followed by 5 mg kg-1 h-1 for 200 min) was administered intravenously in random order to six healthy subjects. After 60 min cholecystokinin (CCK-33) was infused (0.5 i.d.u. kg-' h-1 for 1 h then 1.0 i.d.u. kgtl h-1 for 1 h). Loxiglumide did not change basal levels of CCK and did not augment plasma CCKimmunoreactivity during CCK-33 infusion. After cessation of the CCK-infusion, plasma CCK concentrations decreased rapidly to basal values within 12 min, and the elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…We did so by the minimalist assumption that the mean rate at which EPSPs arrive is proportional to the CCK concentration in plasma, which decays exponentially to zero after bolus injection. The decay of plasma CCK estimated in the current study from the recordings of oxytocin cells (230 seconds) is close to the half-life of CCK measured in human plasma (about 4 minutes) ( 42 ).…”
Section: Discussionsupporting
confidence: 83%
“…We did so by the minimalist assumption that the mean rate at which EPSPs arrive is proportional to the CCK concentration in plasma, which decays exponentially to zero after bolus injection. The decay of plasma CCK estimated in the current study from the recordings of oxytocin cells (230 seconds) is close to the half-life of CCK measured in human plasma (about 4 minutes) ( 42 ).…”
Section: Discussionsupporting
confidence: 83%
“…It was also observed during infusion of the CCK analogue cerulein [22]. When CCK-8 was infused, antagonist treat ment slightly increased plasma CCK concen trations in one study [3], but had no efect in further studies [23,24].…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies we have demonstrated that the first explanation is less likely [33]. However, specific type A CCK-receptors have been demonstrated on SST-producing cells [35], and in a recent study we have demonstrated that inhibition of SST release by CCK-receptor blockade might be the explanation for the augmented BBS-stimulated gastric acid secretion and serum gastrin release during loxiglumide infusion [36].…”
Section: Discussionmentioning
confidence: 88%